2019
DOI: 10.1038/s41598-019-45600-6
|View full text |Cite
|
Sign up to set email alerts
|

Healthy adiposity and extended lifespan in obese mice fed a diet supplemented with a polyphenol-rich plant extract

Abstract: Obesity may not be consistently associated with metabolic disorders and mortality later in life, prompting exploration of the challenging concept of healthy obesity. Here, the consumption of a high-fat/high-sucrose (HF/HS) diet produces hyperglycaemia and hypercholesterolaemia, increases oxidative stress, increases endotoxaemia, expands adipose tissue (with enlarged adipocytes, enhanced macrophage infiltration and the accumulation of cholesterol and oxysterols), and reduces the median lifespan of obese mice. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 66 publications
4
23
0
Order By: Relevance
“…Also, the protective effects of the extract could be related to an increase in the levels of Hsp-70, Hsp-60, and Hsp-27, derived from the activation of heat shock factor 1 (HSF-1). In obese mice, which are characterized by a reduced median lifespan, the longevity-promoting effects of a commercial polyphenol-rich extract were analyzed [193]. Although the treatment did not reverse obesity, it increased the life expectancy of the mice, improved endotoxemia and reduced the degree of inflammation and accumulation in the adipose tissue of cholesterol and cholesterol oxides.…”
Section: Plant Compounds and Longevitymentioning
confidence: 99%
“…Also, the protective effects of the extract could be related to an increase in the levels of Hsp-70, Hsp-60, and Hsp-27, derived from the activation of heat shock factor 1 (HSF-1). In obese mice, which are characterized by a reduced median lifespan, the longevity-promoting effects of a commercial polyphenol-rich extract were analyzed [193]. Although the treatment did not reverse obesity, it increased the life expectancy of the mice, improved endotoxemia and reduced the degree of inflammation and accumulation in the adipose tissue of cholesterol and cholesterol oxides.…”
Section: Plant Compounds and Longevitymentioning
confidence: 99%
“…These data indicate that adipolin may be down-regulated by metabolically unhealthy obesity. It has been shown that obese mice fed a diet supplemented with a polyphenol-rich plant extract induces healthy adiposity and extended lifespan [ 37 ]. Expression profiles of adipokines including adiponectin are reported to differ between metabolically unhealthy and healthy obese individuals [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenol plant extract, composed of Asteraceae, Verbenaceae and Limiaceae was added to the diet at a dosage of 225 mg/kg feed. The AOX extract (Activ’XXS Inside ® supplied by Lara-Spiral, Couternon, France) was analyzed by HPLC and contained 25% polyphenols, including quercetin (3.4%), glycosylated quercetin (5.1%), chlorogenic acid (0.5%), chicoric acid (5.1%) and phenylpropanoids (5%) [ 25 ]. The supplementation rates of the selected plant extracts were based on the producer’s indications regarding the dosage to be employed for humans to obtain health effects.…”
Section: Methodsmentioning
confidence: 99%